Propranolol in treating various symptoms associated with autism spectrum disorder (ASD) - Magdalena Gajkiewicz; Radosław Zaucha; Julia Silldorff; Tomasz Fura; Małgorzata Zając; Marcin Dudek; Zuzanna Felińska; Oliwia Iszczuk; Stanisław Anczyk (Nicolaus Copernicus University in Toruń, 2024)
Introduction and purpose This review provides an in-depth exploration of the pharmacology of propranolol, elucidating its mechanisms of action and clinical implications beyond its conventional indications, contextualizing propranolol's role in ASD management. State of knowledge Propranolol is a non-cardioselective β-adrenergic receptor antagonist, commonly used among the population. Propranolol's mechanisms include reducing cardiac workload, vasoconstriction, and membrane stabilizing properties, which suggest its utility in managing anxiety. ASD, characterized by deficits in social interaction, communication, and repetitive behaviors, affects approximately 1 in 100 children globally. Symptoms often co-occur with anxiety and hyperarousal, linked to noradrenergic system alterations. Review methods Electronic searches were conducted between 6 and 13 May 2024 and included databases: Pubmed and Google Scholar. This review focuses on 4 trials that are limited to years 2016-2024. Conclusions Overall, propranolol shows promise in managing anxiety, enhancing social communication, improving cognitive performance, and addressing severe behavioral challenges in ASD. However, variability in response highlights the need for personalized treatment approaches. Further research is warranted to optimize dosing strategies and understand propranolol's mechanisms, contributing to more effective and tailored treatment options for ASD.